2018
DOI: 10.1021/acs.jpcc.8b05682
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathway of Surface-Catalyzed Ammonia Decomposition and Nitrogen Incorporation in Epitaxial Growth of Gallium Nitride

Abstract: We report density functional calculations that clarify atom-scale mechanisms of vapor-phase epitaxial growth of GaN with gas sources of trimethylgallium and ammonia. We identify various stable adsorption structures of a Ga atom and NH x molecules (x = 0–3) on GaN(0001) surfaces and find that NH2 and NH units spontaneously intervene in Ga–Ga surface bonds on Ga-rich GaN(0001) surface. We then explore the reaction in which NH3 on the surface is decomposed and becomes an N-incorporated structure, −Ga–(NH)–Ga–, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…In this article, we present our efforts to clarify microscopic mechanisms of Metal-Organic Vapor-Phase Epitaxy (MOVPE) of gallium nitride (GaN) [9] based on the DFT calculations. These efforts just get started and preliminary in computics viewpoints but the obtained results are already interesting [10][11][12]. We find that the existence of Ga-Ga weak bonds on the growing surface is essential for the epitaxial growth.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In this article, we present our efforts to clarify microscopic mechanisms of Metal-Organic Vapor-Phase Epitaxy (MOVPE) of gallium nitride (GaN) [9] based on the DFT calculations. These efforts just get started and preliminary in computics viewpoints but the obtained results are already interesting [10][11][12]. We find that the existence of Ga-Ga weak bonds on the growing surface is essential for the epitaxial growth.…”
Section: Introductionmentioning
confidence: 77%
“…We have found two possibilities (Fig. 1): One is on the top Ga atom (T1 site) and the other is on the Ga adtom (Tad site hereafter) [10]. As shown in Fig.…”
Section: Decomposition Of Nh3 and Incorporation Of Nmentioning
confidence: 83%
See 1 more Smart Citation
“…On the theoretical front, recent first principle simulations in our group could provide a detailed atomic-level picture of a Ga rich surface, showing that Ga-Ga weak bond are realized on the exposed surface and these can become active sites for subsequent N incorporation [8,9]. Yet, a fundamental knowledge about both the actual microscopic structure of the Ga-rich growing surface and the NH3 decomposition and incorporation in the growing material at growth temperature is demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Template for JJAP Regular Papers (Jan. 2014)8 both the surface atomic distribution, in terms of PCFs, and the motion of the atoms at the various increasing temperatures, in terms of diffusion coefficients, has revealed that at the experimental growth temperature a two-dimensional liquid state is realized. When this regime is reached, the Ga adatoms incorporated at the surface of the growing structure are rapidly destabilized and their weak bonds with the surface underneath are easily broken.…”
mentioning
confidence: 99%